Relationship between Officer Knowledge and Resources with Healthy Family Index Achievement in Konawe Islands Regency - Mendri, Ni Ketut; Saafi, La Ode; Tasnim, Tasnim (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: Based on the initial data collection, the factors that are obstacles or problems so that the Family Health Index in Konawe Islands Regency has not increased or has not become a healthy status, these factors include knowledge, resources, financing/funding, policies, facilities and infrastructure and so on. For this reason, researchers are interested in conducting research on